Gastric Cancer in the Setting of Persistently Elevated Human Chorionic Gonadotropin: A Case Report - LaToya R. Walker; Brian Erler (Hindawi Limited, 2011)
A 35-year-old woman presented to the emergency room for the evaluation of failed surgical and medical management of a suspected ectopic pregnancy. When imaging studies were performed, she had lymphadenopathy and diffuse sclerosis of the osseous framework. Multiple biopsies were performed and revealed poorly differentiated metastatic carcinoma with signet ring features. Esophagogastroduodenoscopy confirmed the findings of a Stage IV gastric adenocarcinoma. Signs and symptoms of gastric carcinoma are vague. However, to our knowledge, an elevation in human chorionic gonadotropin (hCG) is not an associated finding. Persistence of hCG has many causes from abnormal pregnancy to menopause and other forms of cancer.